Revitalization of the Role of Recently Madrasah Teacher: Modern Learning Perspective and Utilization of ICT in the Globalization Era - Purwowidodo, Agus (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The era of globalization requires strength of human resources (HR) formidable and qualified to play in the global arena. Teaching and learning scenario needs to be prepared carefully in a learning curriculum to improve the quality standards of education, efforts to the implementation of technology, especially information and communications technology (ICT) in the learning system at the school by using the internet in teaching and learning is expected to be able to be implemented more easily, quickly, efficiently, and effectively. By utilizing ICT teachers can create animations or simulations to help students learn abstract concepts, dynamic, and complex. Students can learn, by identifying, developing, organizing, and using all sorts of learning resources. Madrasah teachers also no longer being used as the only one reference of all knowledge but rather as a facilitator or consultant in the learning process and Results in Madrasah.